Hubungan Inovasi Posyandu dengan Keaktifan Kader dan Kunjungan Balita di Posyandu Cempaka Desa Nganguk Kudus - Zulaekah, Niar; Astuti, Dwi; Tristanti, Ika (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
Posyandu (Integrated Health Service Post) is a form of community-based health service aimed at improving health status, particularly for toddlers, pregnant women, and breastfeeding mothers. One of the challenges in managing Posyandu is increasing the number of toddler visits and the activity level of cadres in delivering services. Low toddler visit rates and inactive cadres are common issues faced by Posyandu. The success of Posyandu often depends on the active role of cadres, who are the main drivers of Posyandu activities. The success of Posyandu is significantly influenced by the participation of active and competent cadres.In response to this challenge, Nganguk Village created the